The Seismicity of Lipari, Aeolian Islands (Italy) From One-Month Recording of the LIPARI Array - Di Luccio, Francesca; Persaud, Patricia; Cucci, Luigi; Esposito, Alessandra; Carniel, Roberto; Cortés, Guillermo; Galluzzo, Danilo; Clayton, Robert W.; Ventura, Guido (Frontiers in Earth Science, 2021)
The main goal of this study is to analyze the seismicity of Lipari island (Southern Tyrrhenian sea) in the framework of the dynamic processes affecting the Aeolian islands, including the interaction between pre-existing structures and hydrothermal processes. We deployed a dense seismic array of 48 autonomous 3-component nodes. For the first time, Lipari’s hydrothermal field is investigated by a seismic array recording continuously for about a month in late 2018 with a 0.1-1.5 km station spacing. We analyze the data to understand whether and how the hydrothermal activity affects and controls the seismic signal. We investigate the time evolution of the seismicity, including the cluster distribution over the full time of the experiment using self-organized maps and automatic algorithms. We show that the sea wave motion strongly influences the background seismic noise. Using an automatic template matching approach, we detect and locate a seismic swarm offshore the western coast of Lipari. This swarm, made of transient-like signals, is possibly associated with the activation of a NE-SW fault. We also found the occurrence of hybrid events close to the onshore Lipari hydrothermal system. These events suggest the involvement of hot hydrothermal fluids moving along pre-existing fractures. Array and polarization analysis identify transient signals in the time and frequency domains. Our analyses reveal that Lipari is characterized by seismic signals due to local tectonics, hydrothermal dynamics and sea wave motion during storm events.